Experimental study of the effects of sports tourism on the level of the development of physical training of teenagers - Polkovenko, Olga; Tymchyk, Olesya; Moisak, Aleksandr (ScienceRise: Biological Science, 2017)
Sports tourism in Ukraine is an important component of the general state system of physical culture and sport. The problem of physical training of teenagers, who practice tourism remains for today the most urgent among foreign and native scientists, who study this subject of attention specially and within the research of sports training of young tourists. The study included 46 pupils of 5–6 classes of the following educational institutions: Ss 40 and Ss 170 of the city Kiev with the deep studying of German, the ascertaining experiment took place in 2016. For determining the development level of school children’s physical training there were used valid and reliable methods, which results gave a possibility to collect qualitative and quantitative materials. The criteria of formation of teenagers’ physical culture are: force features; flexibility, endurance; adroitness; ability to jump; speed, - expressed by indicators, which manifestation measure characterizes more or less degree of a criterion expression that, in its turn, helps to determine levels of formation of young teenagers’ physical culture. The authors separated three levels of formation of teenager’s physical culture: high, middle, low. The analysis of the level of physical training of teenagers of I group revealed that 50 % of studied persons have the high level, 36,4 % of interrogated persons have the middle level, 13,6 % of respondents relate to the low one. The diagnostic results of the health level of teenagers of I group demonstrated that 59,1 % of studied persons have the high level, 36,4 % - the middle level, 4,5 % of interrogated persons – the low level. The analysis of the level of physical training of teenagers of II group revealed that 16,7 % of studied persons have the high level, 45,8 % of interrogated persons have the middle level, 37,5 % of respondents relate to the low one